Dispositivo de rescate en altura para liniero en redes de distribución eléctrica de la Corporación Nacional de Electricidad Unidad de negocio Bolívar, en el período 2014. - Terán Ledesma, Marco Vinicio (2016)
The CNEL EP company is an entity that provides a public service of distribution and marketing of electricity within the geographical area and it is concerned and committed to reduce accident statistics specifically in the area of operation and maintenance; which is considered a high risk job; It presents the need to implement a rescue device Height linemen in electricity distribution networks, it is to reduce occupational areas. The device contains the steps of risk management, such as the identification, evaluation and implementation of control risk factors in the study area, in order to achieve the preventive management. Which this device is used to prevent and avoid accidents, so that a technical and statistical analysis is done by using statistical tools that had as an objective to validate the hypothesis of this research project. The annexes to this report specifies in detail the controls implemented to the risk factors identified in the study area, parts of the rescue device, Check List for use of harness, heights rescue instructive controls are based on the compliance with the legislation of Ecuador and international agreements on safety at work is concerned. The 100% of workers, there are 44 workers, in the area of operation and maintenance of CNEL EP. They are linemen performing workers that work at heights, for this reason it is important to emphasize the study reflected in this document as all are exposed to these risks. The objective of this research work is to manage risks in the mechanical lineman job of performing work at height. William Fine method for identifying risk factors in the area of lines and grids of the Corporación Nacional de Electricidad Unidad de Negocio Bolívar. From the results of this investigation it showed the need to improve working conditions, therefore, as part of the personal contribution to this research a rescue device in height was implemented.